Understanding the evolution of human pigmentation: recent contributions from population genetics. - Rees, J; Harding, R (2012)
Variation in human skin and hair color is one of the most striking aspects of human variability, and explaining this diversity is one of the central questions of human biology. Only in the last decade or so has it been realistically possible to address this question experimentally using population genetic approaches. On the basis of earlier studies in mice, and on studies in humans with various Mendelian disorders, many of the genes underpinning population variation in skin color have been identified. More recently, genome-wide approaches have identified other loci that appear to contribute to pigmentary variation. The ability to study sequence diversity from world populations has allowed examination of whether the observed variability is due to random genetic drift or is a result of natural selection. The genetic evidence taken as a whole provides strong evidence for natural selection, functioning so as to increase pigment diversity across the world's populations. Future larger studies are likely to provide more details of this process and may provide evidence for exactly which mechanistic pathways have mediated selection.